Changing the ways we work shaping the ICT-solutions for the next century : proceedings of the Conference on Integration in Manufacturing, Göteborg, Sweden, 6-8 October 1998 - Mȧrtensson, N. (Nils); Mackay, Ronald; Björgvinsson, S. (Advances in design and manufacturing, 1998)
This work highlights the effects of an increasing use of information technology, IT, in manufacturing. The main focus is on the changes in organization, in working procedures and in the demands on the capabilities of personnel, both on the shop floor and the engineering and management levels.